Supply and utilization of food crops in Ghana, 1960- 2000 - Codjoe, S.N.A. (African Journal of Food Agriculture, Nutrition and Development 2(7): 1-15, 2007)
Agriculture is the main economic activity of the majority of the population living in Ghana. It contributes over 40% of Gross Domestic Product and employs about half of Ghana’s labour force. Due to that much attention has been placed on sustainable management of agricultural resources in the country. About 13,628,179 hectares representing 57.1% of Ghana’s total land area of 23,853,900 hectares, is suitable for agriculture. However, total area under cultivation in 2000 was 5,808,600 hectares representing 42.6% of the agricultural area. Agriculture in Ghana is mainly on a smallholder basis, although there are some large farms and plantations, particularly for cocoa (1,200,000 ha); oil palm (285,000 ha); seed cotton (62,000 ha); tobacco (1,600 ha); and coconut, banana, kola, etc. (1,502,500 ha). The main system of farming is traditional with the use of hoe and cutlass. Even though there is little mechanised farming, subsistence farming is widespread, especially in northern Ghana. In the 1970s, Ghana was virtually self sufficient in the production of maize, cocoyam, cassava, and plantain. In 1981-1983, the demand for all these crops except cassava exceeded production. From 1969 to 1983, annual total agricultural production declined by almost 1% while per capita production declined almost 4%. Food supply per person dropped almost 30%. Supply (import and export) and utilisation (for food, feed, seed, farm manure, waste and other uses) of food crops have consequences for food production in Ghana. Using data from the Food and Agriculture Organisation and the Ghana Ministry of Food and Agriculture Census, this paper assesses production, supply and utilisation of food crops in Ghana from 1960 to 2000. It also assesses the trend and pattern of population growth for the same period. Multiple regression models are used to ascertain the statistically significant predictors of food crop (rice, maize, millet, sorghum, cassava, yam and plantain) production in five periods, namely 1960s, 1970s, 1980s, 1990s and 2000s. The analysis shows that wastage, food imports, growth in human population, the utilisation of certain food crops as feed, food and on farms as manure, significantly influenced the production of food crops in Ghana at one point in time or the other in the five decades.
Keywords: Supply; Utilisation; Food crops; Ghana; Sub-Saharan Africa